Maize grain yield and grain zinc concentration response to zinc fertilization: A meta-analysis - Mutambu, Dominic; Kihara, Job Maguta; Mucheru-Muna, Monicah; Bolo, Peter Omondi; Kinyua, Michael (Elsevier, 2023)
Zinc deficiency in agricultural soils is a current global agroecosystems challenge. Maize exhibits elevated susceptibility to Zn deficiency and low response to zinc fertilization. As a result, there are contradicting literature reports on the crop response to zinc fertilization. This meta-analysis synthesized the current evidence on maize response to zinc fertilization from different studies and highlighted the potential innovations to improve the crop response to zinc application. Systematic literature searches were conducted on the Web of Science and Google Scholar for peer-reviewed publications. From the selected publications, data extracted were maize grain yield and maize grain zinc concentration. The meta-analysis was conducted in R statistical environment using the metafor package. The ratio of means was the chosen effect size measure used. The assessment of effect size heterogeneity showed that the study effect sizes were significantly heterogeneous and also publication bias was evident. The analysis showed 17% and 25% maize grain yield and grain zinc concentration response to zinc fertilization. As a result, zinc fertilization was associated with yield increments of up to 1 t ha-1 and 7.19 mg kg-1 grain zinc concentration over the control (no zinc application). Despite the observed maize grain response to zinc application, the median concentration of grain Zn was below the 38 mg kg-1 recommended maize grain zinc concentration to combat human zinc deficiency (hidden hunger). As a result, potential innovations likely to achieve sufficient maize grain zinc content were highlighted including the use of nano-particulate zinc oxide, foliar zinc application, timing of zinc application, precision fertilization and zinc micro-dosing. Due to scanty literature on the progress of these innovations in maize, follow-up studies are recommended to evaluate their potential success in the agronomic bio-fortification of maize with zinc.